The Influence Of Leverage, Dividend Per Share, And Cash Flow Volatility On Hedging Decisions (Empirical Study of Manufacturing Companies in the Food and Beverage Industry Sub-Sector Listed on the IDX for the 2019-2021 Period) - Hernadianto Hernadianto; Indri Permata Sari (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to examine the effect of leverage, dividend per share and cash flow volatility on hedging decisions in food and beverage companies listed on the IDX during 2019-2021 which were selected based on certain criteria using purposive sampling. This research uses secondary data in the form of annual reports of food and beverage companies listed on the IDX during 2019-2021. The sample in the company is 25 x 3 years of research and the total sample is 75. The type of research used is quantitative research, the data used in this research is secondary data in the form of financial reports listed on the IDX. The analytical method used is logistic regression analysis which is processed using the SPSS program. The results showed that: leverage has no significant effect on hedging decisions. Dividend per share has no significant effect on hedging decisions. Cash flow volatility affects hedging decisions. The results of the study simultaneously leverage, dividend per share, and cash flow volatility variables influence hedging decisions. Keywords : Leverage, Dividend Per Share, Cash Flow Volatility, and Hedging Decisions.